Sporting activity after craniosynostosis surgery in children: a source of parental anxiety - Rotimi, Oloruntobi (Childs Nerv Syst, 2020)
PURPOSE: Craniosynostosis correction involves major skull surgery in infancy—a potential source of worry for parents when their treated children begin involvement in sports. METHODS: Electronic multiple choice survey of parents of children who had undergone craniosynostosis surgery in infancy using 5-point Likert scales. RESULTS: Fifty-nine completed surveys were obtained from parents of children who had undergone previous craniosynostosis surgery. Mean age of children was 7.8 years (range 3 months to 22 years), with 36 non-syndromic and 23 syndromic cases. The most common surgery was fronto-orbital remodelling (18). Fifty-two of 59 were involved in athletic activity. The most intense sport type was non-contact in 23, light contact in 20, heavy contact in 4 and combat in 5. Participation level was school mandatory in 12, school club in 17, non-school sport club in 21 and regional representative in 2. One child had been advised to avoid sport by an external physician. Mean anxiety (1–5 Likert) increased with sport intensity: non-contact 1.7, light contact 2.2, heavy contact 3.5 and combat 3.6. Twenty-nine of 59 parents had been given specific advice by the Craniofacial Team regarding athletic activity, 28 of which found useful. Three sport-related head injuries were reported, none of which required hospitalisation. CONCLUSION: Little information exists regarding sports for children after craniosynostosis surgery. This study suggests that parental anxiety remains high, particularly for high impact/combat sports, and that parents would like more information from clinicians about the safety of post-operative sporting activities.